Binding behaviors of para-dicyclohexanocucurbit[6]uril and meta-tricyclohexanocucurbit[6]uril with dialkyl viologens. Issue 8 (3rd August 2018) - Shi, Hao; Zheng, Li-Mei; Lin, Rui-Lian; Fang, Guo-Sheng; Sun, Wen-Qi; Liu, Jing-Xin
Abstract: The binding behaviours of para -dicyclohexanocucurbit[6]uril (Cy2 Q[6]) and meta -tricyclohexanocucurbit[6]uril (Cy3 Q[6]) with a series of dialkyl viologens (MV 2+, EV 2+, PV 2+, BV 2+, FV 2+ and HV 2+ ) have been investigated by various methods. In the aqueous solution, 1 H NMR spectra suggest that the alkyl chains are more favourably encapsulated into the hydrophobic cavities of both hosts than the aromatic rings. Cyclic voltammograms (CV) curves show that the Cy2 Q[6] or Cy3 Q[6] bind the charged viologens more strongly than the reduced viologens. Isothermal titration calorimetry (ITC) data reveal that the binding processes of both hosts with viologens are enthalpic driven. In the solid state, the PV 2+, BV 2+ guests and two Cy3 Q[6] hosts generated dumbbell-shaped structures, with two Cy3 Q[6] hosts residing over two terminal alkyl chains of the guests. Abstract : Binding behaviors of para -dicyclohexanocucurbit[6]uril and meta -tricyclohexanocucurbit[6]uril with six dialkyl viologens were investigated by various tools, indicating that the driving forces of the formation of the host−guest inclusion complexes result from the cooperativity of the hydrophobic effect, ion−dipole interaction and van der Waals interaction.